Embedded Device pada Smarthome System Berbasis IoT untuk Pengoperasian Pintu Gerbang Terkendali melalui Smartphone - Ahmad Fauji; Arief Goeritno; Lucky Hardian; Bayu Arief Prakoso (Universitas Syiah Kuala, 2022)
This research was motivated by a number of shortcomings in previous similar studies, mainly related to the selection of sensors, the selection of application for operation, and the absence of backup power in the system, so that manufacturing and development were carried out for the acquisition of an embedded device as a control unit. The availability of this control unit is part of the smart-home system based on the Internet of Things (IoT) for gateway controllers, via smartphones with a one-time password mechanism. The research objectives include (i) the manufacture of control units and programming based on Arduino IDE and (ii) verification and validation tests. The realization of the control unit is carried out through assembling a number of electronic devices, making motherboards, re-functionalizing of the miniature gates, and integrated wiring equipped with embedded programs. The performance of the control unit is measured by providing verification tests in the form of simulations based on the Proteus application and validation tests assisted by the Telegram Bot application when conditions are given to the gate when it is opened, closed, or the lock is in a lock/unlocked state. The performance of the control unit developed, in the form of increasing the speed of the gate opening and closing process, implementing one-time passwords for operating security, and the availability of internal backup power. Recommendations for further research, more emphasis is placed on the creation of various control units that are integrated into the smart-home system platform.